One-pot synthesis of nickel nanoparticles-embedded biochar and insight on adsorption, catalytic oxidation and photocatalytic oxidation of dye - Is Fatimah; Galih Dwiki Ramanda; Suresh Sagadevan; Suratno; Muchammad Tamyiz; Ruey-an Doong (Case Studies in Chemical and Environmental Engineering, 2024)
In this study, nanocomposite of nickel nanoparticles-embedded biochar (Ni@BC) was prepared by one-pot pyrolysis method. The role of Ni content to the physicochemical character relevant to adsorption, catalytic oxidation and photocatalytic oxidation activities of the nanocomposite was investigated. The instrumental analyses using X-ray difraction (XRD), scanning electron microscope-energy dispersive x-ray fluorescence (SEM-EDX), transmission electron microscope (TEM), vibrating sample magnetometry, X-ray photoelectron spectroscopy (XPS), and gas sorption analysis were employed to analyze the features of nanocomposite, meanwhile the photocatalytic oxidation of methyl orange (MO) was chosen to evaluate the photocatalytic performance of the nanocomposite. The instrumental analysis results suggest that single phase of dispersed-nickel nanoparticles onto biochar structure was obtained by Ni content of 5, 10, and 30 % wt. With a mean particle's size of 50 nm. From XRD analysis, it was obtained that the higher Ni content in the nanocomposite leads to create higher crystallite size, where the Ni content of 5, 10, and 30 %wt. Gave the size of 18.7, 27.8, and 29.5 nm, respectively. The samples exhibited magnetism with saturation magnetization (Ms) ranging at 3.87 emu g−1- 9.87 emu, which the higher Ni content result in higher magnetism. Similarly, higher Ni content corresponded to a higher specific surface area. Highly photoactivity and stability of Ni@BC was expressed by complete (100 %) methyl orange removal for 30 min, and recyclability until 5th use without appreciable physicochemical properties of the nanocomposite.